1992
DOI: 10.1128/jb.174.2.601-609.1992
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties and evolutionary relationships of PspA, a surface protein of Streptococcus pneumoniae, as revealed by sequence analysis

Abstract: Analysis of the sequence for the gene encoding PspA (pneumococcal surface protein A) of Streptococcus pneumoniae revealed the presence of four distinct domains in the mature protein. The structure of the N-terminal half of PspA was highly consistent with that of an a-helical coiled-coil protein. The a-helical domain was followed by a proline-rich domain (with two regions in which 18 of 43 and 5 of 11 of the residues are prolines) and a repeat domain consisting of 10 highly conserved 20-amino-acid repeats. A fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
185
0
18

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(208 citation statements)
references
References 65 publications
5
185
0
18
Order By: Relevance
“…Based on a single difference in reactivity with a panel of monoclonal antibodies, the D39 and WU2 PspAs are classified in different serotypes (serotypes 25 and 1, respectively) (9). The pspA sequences of the D39 derivatives Rx1 and R6 have been reported previously and exhibit complete identity (22,43). A comparison of the predicted N-terminal halves of the WU2 and Rx1 PspA sequences showed that despite a number of differences, the PspAs were closely related and were members of the same PspA clade (21).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Based on a single difference in reactivity with a panel of monoclonal antibodies, the D39 and WU2 PspAs are classified in different serotypes (serotypes 25 and 1, respectively) (9). The pspA sequences of the D39 derivatives Rx1 and R6 have been reported previously and exhibit complete identity (22,43). A comparison of the predicted N-terminal halves of the WU2 and Rx1 PspA sequences showed that despite a number of differences, the PspAs were closely related and were members of the same PspA clade (21).…”
mentioning
confidence: 94%
“…The C-terminal coding region of WU2 pspA was targeted and cloned essentially as described previously for Rx1 pspA (45). The WU2 derivative JY1123 was constructed by transformation and insertion of pKSD300, which harbors an internal 550-bp fragment from the 5Ј half of Rx1 pspA in pVA891(Em) (36,43,45). Chromosomal DNA from JY1123 was digested with HindIII, self-ligated, and transformed into E. coli, with selection for erythromycin-resistant transformants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A capsular type 3 pneumococcal strain (WU2, PspA ϩ ) (24,25) and its isogenic mutant (JY1119, PspA Ϫ ) (4,7,26) were used. Bacterial stocks were frozen at Ϫ80°C in Todd-Hewitt broth supplemented with 0.5% yeast extract containing 10% glycerol.…”
Section: Bacteria and Infectionsmentioning
confidence: 99%
“…The PspA molecule is built from four distinct domains which include the antigenic N-terminal part followed by a highly flexible, tetherlike proline-rich region, a repeat region which is responsible for the attachment to the choline residues, and a C-terminal hydrophobic tail ( Fig. 1) (17). The N-terminal moiety likely protrudes outside of the capsule, interacts with all antibodies reactive to PspA, and has been described as the functional part of this protein (the PspA function was defined as its ability to elicit in host protective antibodies) (18,19).…”
mentioning
confidence: 99%